Investigating bracovirus chromosomal integration and inheritance in lepidopteran host and nontarget species. Issue 21 (20th September 2022) - Muller, Héloïse; Heisserer, Camille; Fortuna, Taiadjana; Mougel, Florence; Huguet, Elisabeth; Kaiser, Laure; Gilbert, Clément
Abstract: Bracoviruses (BVs) are domesticated viruses found in braconid parasitoid wasp genomes. They are composed of domesticated genes from a nudivrius, coding viral particles in which wasp DNA circles are packaged. BVs are viewed as possible vectors of horizontal transfer of genetic material (HT) from wasp to their hosts because they are injected, together with wasp eggs, by female wasps into their host larvae, and because they undergo massive chromosomal integration in multiple host tissues. Here, we show that chromosomal integrations of the Cotesia typhae BV (CtBV) persist up to the adult stage in individuals of its natural host, Sesamia nonagrioides, that survived parasitism. However, while reproducing host adults can bear an average of nearly two CtBV integrations per haploid genome, we were unable to retrieve any of these integrations in 500 of their offspring using Illumina sequencing. This suggests either that host gametes are less targeted by CtBVs than somatic cells or that gametes bearing BV integrations are nonfunctional. We further show that CtBV can massively integrate into the chromosomes of other lepidopteran species that are not normally targeted by the wasp in the wild, including one which is divergent by at least 100 million years from the natural host. Cell entry and chromosomal integration of BVs are thus unlikely to be major factors shaping wasp host range. Together, our results shed new light on the conditions under which BV‐mediated wasp‐to‐host HT may occur and provide information that may be helpful to evaluate the potential risks of uncontrolled HT associated with the use of parasitoid wasps as biocontrol agents.